(untitled) (Bangladesh Journal of Agriculture, 2023)
Lentil is an important legume crop grown by three or four time tillage operations with post sowing irrigation after monsoon rice harvest. Strip tillage is a climate smart tillage technology where residual soil moisture can be utilized for plant growth and development. This study was conducted at Regional Agricultural Research Station, Ishurdi, Bangladesh in two consecutive years of 2020 and 2021 to find out the optimum row spacing for specific lentil variety under strip tillage seeding system. Four row spacing (S1= 20 cm, S2= 25 cm, S3= 30 cm, S4= 40 cm) and three varieties of lentil (V1= BARI Masur-8, V2= BARI Masur-7, V3= BARI Masur-6) were assigned in a factorial Randomize Complete Block Design with three replications. The trend of lentil seed yield was recorded as BARI Masur-8 > BARI Masur-7 > BARI Masur-6 and seed yield decreased with increasing row spacing for all varieties. The results showed that 25 cm row spacing for BARI Masur-8, 20 cm row spacing for BARI Masur-6 and BARI Masur- 7 were found suitable row spacing at strip tillage seeding systems. Among the lentil varieties, BARI Masur-8 showed better performance than others due to higher yield attributes and seed yield. Bangladesh J. Agri. 2022, 47(2): 97-106